Pengaruh Pelatihan Profesioanal Pedagogik Guru Terhadap Keterampilan Mengajar - Rangga Hasibuan; Lili Raflika; Ariana Ariana; Fikri Hamdi Siregar; Dara Avira; Hasyim Basid; Inom Nasution (LPPM Politeknik Pratama, 2023)
This research aims to investigate the influence of professional pedagogical training on teachers’ teaching skills in schools. In an effort to improve the quality of education, many educational institutions have provided pedagogical training to their teachers. This study aims to measure whether such training has a positive impact on teachers’ teaching skills. The results showed that teachers who took pedagogical training had significant improvements in teaching skills compared to the control group. They are better able to plan effective learning, manage the class well, and interact with students positively. Apart from that, they also have a higher level of motivation in teaching. These findings suggest that pedagogical professional training can have a significant positive impact on teachers’ teaching skills. Therefore, it is recommended that educational institutions continue to encourage and provide relevant and useful pedagogical training for their teachers. This can contribute to improving the quality of education and student learning experiences.